Induction of hepatic miR-34a by perfluorooctanoic acid regulates metabolism-related genes in mice. (January 2019) - Cui, Ruina; Li, Chenyang; Wang, Jianshe; Dai, Jiayin
Abstract: Perfluorooctanoic acid (PFOA) is a widespread organic pollutant with various toxicological impacts on the liver. Members of the miR-34 family are P53-targeted growth suppressors. We found that PFOA exposure (5 mg/kg/d PFOA for 28 d) resulted in a significant increase of miR-34a in the livers of mice but had no effect on either miR-34b or miR-34c. We knocked out miR-34a in mice to explore the role of elevated miR-34a in PFOA-induced liver toxicity. Compared with the corresponding untreated control, significant increases in liver weight as well as serum alanine transaminase, aspartate aminotransferase, and cholinesterase levels were observed in miR-34a −/− and wild-type mice after PFOA exposure. Hepatic cells showed similar swelling in both miR-34a −/− and wild-type mice after PFOA treatment. Hepatic RNA-sequencing (RNA-seq) showed that PFOA led to significant alteration in lipid metabolism genes, especially those involved in the peroxisome proliferator-activated receptor pathway, in both wild-type and miR-34a null mice. With or without PFOA treatment, relatively fewer genes were altered in miR-34a −/− livers compared to wild-type livers. Among the changed genes by miR-34a, the most dominant were metabolism-related genes, such as Fabp3, Cyp7a1, and Apoa4. Our in vivo study indicated that miR-34a mainly exerts a metabolic regulation role, rather than the pro-apoptosis and cell cycle arrest role reported previously by many in vitro studies. In addition, although hepatic P53 was unchanged, the active type of P53 (acetylated P53 (acetyl-p53, Lys379)) was markedly altered under PFOA treatment. Therefore, the increase in acetylated P53 may have activated the transcription of miR-34a in mouse livers after PFOA treatment. Graphical abstract: Image 1 Highlights: PFOA exposure increased miR-34a and induced acetylation of P53 in the liver. Hepatomegaly was observed in both miR-34a and wild-type mice. MiR-34a had no pro-apoptosis or cell cycle arrest effect in the liver. MiR-34a mainly regulated the expression of metabolism genes in the liver. Abstract : Our study provides novel knowledge on the hepatic hazard of PFOA exposure, suggesting that miR-34a contributes to lipid metabolism regulation role under PFOA exposure.